Periodic Solutions of Some Impulsive Hamiltonian Systems with Convexity Potentials - Dezhu Chen; Binxiang Dai (Abstract and Applied Analysis)
We study the existence of periodic solutions of some second-order Hamiltonian systems with impulses. We obtain some new existence theorems by variational methods.